Justification of Statutory Service Life Extension of Locomotives on the Basis of Theory of Aging - Krashenin, Oleksandr; Klymenko, Oleksandr; Ponomarenko, Olena; Yakovlev, Serhii (International Journal of Engineering and Technology, 2018)
The article is devoted to statutory service life extension of locomotives on the basis of mathematical methods and provisions of the following theories: reliability, games, probability, aging, pattern recognition, and others. Methods of reliability theory have been used to simulate a system of repairs and critical assessment of options for organization of maintenance and repair in excess of statutory service life of locomotives. Methods of game theory are used to determine the tactics of locomotive maintenance over normative term of use. Methods of probability theory and mathematical statistics are used for collecting and processing initial data, the laws of distribution of random variables of working properties and loads are determined in the calculation of the reliability of bearing structures of locomotives, as well as the effectiveness of replacing the old rolling stock with a new one. Methods based on the theory of aging to determine values of criteria for estimating boundary terms for various variants of the strategy of prolonging the operation of locomotives in excess of the normative term. Methods of pattern recognition theory are used to adjust the system of obtaining locomotives in excess of the normative lifetime.Â
Keywords: Maintenance; Non-routine Maintenance; Statutory Service Life Extension; Theory of Reliability; Theory of Aging